Reasons for default and death among tuberculosis cases treated under revised national tuberculosis control program in selected tuberculosis units of Bangalore urban district of Karnataka state - M. P., Srinath (International Journal Of Community Medicine And Public Health, 2018)
Background: Tuberculosis (TB) is a disease of great antiquity. Mycobacterium tuberculosis is a formidable pathogen. Tuberculosis still remains a worldwide problem, despite the facts that proper medications are available to treat the condition. Defaulting from the treatment is a serious issue in the treatment failure. The current study was undertaken to understand the default rate, death and its reasons among the TB patients who underwent treatment in two selected DOTS centre at Bangalore Urban district of Karnataka state. Methods: A cross-sectional study was conducted on 160 default patients treated under RNTCP at two randomly selected TB centres. The interview was conducted using a semi-structured questionnaire. Patient's relatives were interviewed in case of deaths. Appropriate statistics were used to find the significance. Results: Among the total study subjects, the 75% of the cases were males, 71.9% were in the age group 15-44 years. More than 46% of the patients were registered in category-1. The study observed that 70% of the patients defaulted during the continuation phase and only 30% defaulting was observed in the initial phase. Migration, side effects of the drugs and alcohol addiction were the major reasons for discontinuing from therapy. Maximum death (52%) was observed among Cat-1 followed by Cat-2 and the highest death rate was observed among >45 years age group. Conclusions: The study concludes that the default was prevalent among the study population, migration and untoward effects of the drugs were the important factors of default.